Unravelling sex-dependent mechanisms in calcific aortic valve stenosis. (10th June 2022) - Moschetta, D; Massaiu, I; Valerio, V; Bozzi, M; Myasoedova, V; Poggio, P
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Italian Ministry of Health Background: Calcific aortic valve stenosis (CAVS) is the most common heart valve disease that affects 3% of the population. CAVS is a progressive, multifactorial disorder driven by several cellular and molecular pathological processes. Currently, there is no pharmacological therapy able to prevent CAVS progression. Little is known about the sex-related difference in molecular mechanisms. Recent studies reported that men showed a higher aortic valve calcium load than women, which in turn, developed more fibrosis in the stenotic aortic valve leaflets. Hence, it has been hypothesized that the mechanisms underlying CAVS progression could be different between the two sexes. Purpose: To investigate sex-differences in CAVS molecular pathways, finding new sex-related pharmacological targets. Methods: Valve interstitial cells (VIC) were isolated from 26 patients who underwent aortic valve replacement for aortic valve stenosis. RNA, extracted from VICs, was sequenced by third generation sequencing technology. We performed pro-fibrotic (TGFβ) treatment for 5 days and we evaluated soluble collagen expression by a colorimetric assay and αSMA expression by western blot. We evaluated extracellular calcium extent by a colorimetric assay on VICs exposed to pro-calcific (inorganic phosphate) medium for 7 days. We assessed the mitochondrial damage with mitoSOX staining by Imagestream. Results: The gene expression analysis from sequenced VICs revealed 65 genes upregulated in men and 89 genes upregulated in women. The functional analysis showed that the TGFβ signaling resulted enriched in woman VICs, while the mitochondrial related genes were upregulated in man VICs. Only woman VICs secreted higher amount of collagen under TGFβ treatment respect to the untreated (1.22±0.03 fold change (FC) vs. untreated, p<0.001). αSMA expression (marker of VICs activation) was significantly higher both in men and women exposed to different concentrations of TGFβ (TGFβ 5ng/ml: 1.88±0.34 in men and 2.66±0.32 in women, FC vs. untreated, p=0.003 and p<0.0001, respectively; TGFβ 10ng/ml: 2.96±0.55 in men and 2.16±0.35 in women, FC vs. untreated, p=0.0003 and p=0.0006, respectively). The calcification potential of VICs exposed to pro-calcific medium was higher in men than in women (8.23±0.45 vs. 4.69±0.59 FC vs. untreated, respectively, p<0.0001). The mitochondrial superoxide formation in man VICs was higher than in woman VICs at steady state (51.0±2.1% vs. 29.5±0.9% of positive cells, respectively, p<0.0001) Conclusion: CAVS progression seems to be driven by sex-dependent molecular pathways activation. In particular, pro-fibrotic pathways are upregulated in women, while pro-calcific pathways and mitochondrial damage in men. Our data pave the way to sex-dependent pharmacological target research, aiming to treat CAVS patients.